Racial and ethnic discrimination in local consumer markets: exploiting the army's procedures for matching personnel to duty locations - Heather Antecol; Deborah A. Cobb-Clark (Institute for the Study of Labor (IZA), 2006)
We use the exogenous assignment of Army personnel to duty locations to analyze the relationship between the characteristics of local markets and the propensity for consumers to be subjected to racial discrimination in their everyday commercial transactions. Overall, one in ten soldiers report that they or their families have experienced racial discrimination in finding non-government housing or in patronizing businesses in their local communities. Discrimination is related to a community's demographic profile with white and Asian soldiers feeling more unwelcome in local businesses as the local population becomes more heavily weighted towards other groups. Moreover, there is evidence that increased economic vulnerability in the community results in more housing discrimination amongst minorities. While the evidence that increased competition reduces consumer market discrimination is mixed, it is clear that discrimination is related to the nature of a soldier's interaction with the local community.
urn:nbn:de:101:1-2009040687
Keywords: 330